2022
DOI: 10.3390/ma15041510
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Temperature Distribution in Concrete under Variable Environmental Factors through a Three-Dimensional Heat Transfer Model

Abstract: Temperature distribution in concrete is significant to the concrete structure’s macro properties and different factors affect the heat transfer in concrete, and therefore influence the temperature distribution. This work established a three-dimensional transient heat transfer model coupled with various environmental factors, using the finite element method for calculating the results and real-measured data for testing accuracy. In addition, a sensitivity evaluation of various factors was conducted. Due to vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Yingshu Yuan [14] et al, in order to predict the temperature response of concrete in natural climatic environments, a model based on the heat conduction of concrete proposed by considering the natural weather variations induced by diurnal and seasonal temperatures, and based on the extreme value of the Difference Decomposition, gave a method to deal with climatic temperature data, and the results showed that the prediction model can be more effective in predicting the temperature response of concrete under natural environment.MP Dissanayaka [23] et al, applied the finite element method and the finite difference method to the concrete temperature prediction model, and found that applying these two methods to predict the temperature of concrete is more effective, and emphasized the importance of cold water pipe is important for the cooling of concrete structure, but the calculation method is more complicated and can not be applied to the long-term prediction of concrete temperature. Haoyu Zeng [24] et al, studied and established a three-dimensional transient heat transfer model, calculated the model using the finite element method, and compared and analyzed the calculation results with the measured data. The results showed that: the prediction of temperature distribution in concrete by the three-dimensional model was relatively accurate, with an error of less than 4%; the surface temperature difference in July was twice as much as that in December; the wind speed had a cooling effect on the surface of the concrete, and the larger the wind speed was, the stronger the cooling effect was.…”
Section: Introductionmentioning
confidence: 99%
“…Yingshu Yuan [14] et al, in order to predict the temperature response of concrete in natural climatic environments, a model based on the heat conduction of concrete proposed by considering the natural weather variations induced by diurnal and seasonal temperatures, and based on the extreme value of the Difference Decomposition, gave a method to deal with climatic temperature data, and the results showed that the prediction model can be more effective in predicting the temperature response of concrete under natural environment.MP Dissanayaka [23] et al, applied the finite element method and the finite difference method to the concrete temperature prediction model, and found that applying these two methods to predict the temperature of concrete is more effective, and emphasized the importance of cold water pipe is important for the cooling of concrete structure, but the calculation method is more complicated and can not be applied to the long-term prediction of concrete temperature. Haoyu Zeng [24] et al, studied and established a three-dimensional transient heat transfer model, calculated the model using the finite element method, and compared and analyzed the calculation results with the measured data. The results showed that: the prediction of temperature distribution in concrete by the three-dimensional model was relatively accurate, with an error of less than 4%; the surface temperature difference in July was twice as much as that in December; the wind speed had a cooling effect on the surface of the concrete, and the larger the wind speed was, the stronger the cooling effect was.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature field of concrete structures can be affected by various environmental factors, and some necessary environmental factors, such as solar radiation, air convection, and heat conduction, have been widely considered in the prediction of concrete temperature 25 27 . Zhang et al 28 conducted wind tunnel tests on the convective heat transfer coefficient of concrete surfaces and proposed a relationship between the convective heat transfer coefficient and the wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…Yingshu Yuan [14] et al, to predict the temperature response of concrete in natural climatic environments, a model based on the heat conduction of concrete is proposed by taking into account the natural weather variations induced by diurnal and seasonal temperatures, and based on the extreme value of the Difference Decomposition, gave a method to deal with climatic temperature data, and the results showed that the prediction model can be more effective in predicting the temperature response of concrete under natural environment.MP Dissanayaka [23] et al, applied the finite element method and the finite difference method to the concrete temperature prediction model, and found that applying these two methods to predict the temperature of concrete is more effective, and emphasized the importance of cold water pipe is important for the cooling of concrete structure, but the calculation method is more complicated and can not be applied to the long-term prediction of concrete temperature. Haoyu Zeng [24] et al, studied and established a three-dimensional transient heat transfer model, calculated the model using the finite element method, and compared and analyzed the calculation results with the measured data. The results showed that: the prediction of temperature distribution in concrete by the three-dimensional model was relatively accurate, with an error of less than 4%; the surface temperature difference in July was twice as much as that in December; the wind speed had a cooling effect on the surface of the concrete, and the larger the wind speed was, the stronger the cooling effect was.…”
Section: Introductionmentioning
confidence: 99%